Peran Guru PAI Dalam Mendidik Karakter Di Sekolah SMP Al-Huda Jatimulyo - Deni Riski Setiawan (Moral : Jurnal kajian Pendidikan Islam, 2025)
The role of Islamic Religious Education teachers has a very important position in education, so that in this study the role of Islamic Religious Education teachers in educating character at Al-Huda Middle School, Jatimulyo is described. The purpose of this study is to determine the role of Islamic Religious Education teachers in educating character at Al-Huda Middle School, Jatimulyo. The method used in this study is a field research type reviewed from the method and level of discussion, so this study is classified as descriptive research. Data collection methods used in this study are interviews, observations, and documentation. The results of this study show 3 important parts of the teacher's role, namely teachers as educators such as role models in every movement of an Islamic religious teacher in their daily lives. The role of teachers as educators is implemented through teachers in speech; saying good and correct words, speaking gently and politely, teachers in deeds. The implementation of Islamic Religious Education Values ​​at Al-Huda Middle School Jatimulyo is implemented through the instillation of character values ​​such as congregational prayer, welcoming students at the school gate, becoming a prayer leader, social concern, which is seen when teachers raise funds for our brothers and sisters who are affected by disasters or calamities.